Ist einer unter Ihnen, der seine ganze Bestimmung noch nicht fühlt - Gibbons, J; James Gibbons (2000)
﻿ The present thesis traces Lenz's development during the decisive period of 1774-76, focusing on his own sense of 'Bestimmung' as a writer. The method adopted has a dual aspect. Firstly, a substantial number of unpublished manuscripts related to Lenz's military reform project, written during his stay in Weimar - widely acknowledged as the 'Wendepunkt' of his career - are edited and analysed for the first time. Secondly, these manuscripts will be read in conjunction with a series of existing texts so as to give an overview of the process of Lenz's development. 1774 is a pivotal date, for in Meinungen eines Laien Lenz sets what he himself terms the 'Grundstein' of his entire oeuvre. A close analysis of this much ignored text is key to an understanding of the ethos which underpins his subsequent development. At its conclusion Lenz also articulates his desire to play a more active role in society than the limitations of literature allow. It is with his military reform project that Lenz hopes to effect such a transition. Die Soldaten is read as an initial attempt to voice his ambition of gaining a position in court. Such a reading has only been made possible by the edition of a number of manuscripts from the Kraków Lenziana. Thus the thesis seeks to fill a vital gap in Lenz scholarship: an investigation into Lenz's political aspirations as reflected in his writings whilst in Weimar, and particularly during his stay in his Berka 'Einsiedelei'. An understanding of the historical events, particularly those unfolding in France, which gave rise to the project is long overdue and is addressed here in the analysis of the 'lettre à Maurepas'. Der Landprediger, written after his expulsion from Weimar following his notorious 'Eseley' of November 1776, is read as an epitaph to Lenz's abortive career of writer as reformer.